A potential spice with multifunctional pharmacological properties can prevent COVID-19 disease - Banerjee, Subha Bose (International Journal of Research in Medical Sciences, 2021)
Novel coronavirus disease (COVID-19) is the major health crisis in the world. World Health Organisation has declared COVID-19 as a global pandemic. There are no effective drugs to treat COVID-19 infection. Till date include remdesivir, umifenovir, favipiravir, lopinavir/ritonavir, ribavirin, hydroxychloroquine, etc. are used to treat this disease. There is an urgent need for public health measures, not only to limit the spread of the virus, but also to implement preventive approaches to control severe COVID-19 disease. Most drugs on the market have shown unwanted symptoms and toxic effects related to these drugs. In this situation people are searching for safe herbal extracts and pharmacologically active molecules having numerous therapeutic properties. Garlic (Allium sativum L.; Family: Amaryllidaceae) is an aromatic herbaceous annual spice with numerous therapeutic properties. Garlic is one of the most efficient natural antibiotics against the wide spectrum of viruses and bacteria. Organosulfur (e.g. allicin and alliin) and flavonoid (e.g. quercetin) compounds are responsible for immunomodulatory effects of this healthy spice. The viral replication process is accelerated with the main structural protease of severe acute respiratory syndrome corona virus-2 (SARS-CoV-2). The formation of hydrogen bonds between this serine-type protease and garlic bioactives in the active site regions inhibits the COVID-19 outbreak. Intake of garlic and its derived-products in regular diet as an adjuvant therapy may minimise side effects and toxicity of the main therapeutic drugs of COVID-19 infection.